An Introduction to Business Ethics - Desjardins, Joseph (Boston : McGrow-Hill Higher Education, 2009)
Business
Keywords: Business Ethics; Social Responsibility; International Business; Globalization; Business Environment; Marketing Ethics; Product Safety; Employee Responsibilities; Moral Rights; corporate Culture; Corporate Social Responsibility